1999
DOI: 10.1097/00001888-199904000-00011
|View full text |Cite
|
Sign up to set email alerts
|

The University of Louisville Medical Schoolʼs comprehensive programs to increase its percentage of underrepresented-minority students

Abstract: Since 1981, the University of Louisville (U of L) School of Medicine has developed several programs to increase the number of its underrepresented-minority (URM) matriculants and help them succeed during their medical education. The first such effort, begun in 1981, was the Professional Education Preparation Program for Kentucky high school students from underserved counties. Programs in Louisville's elementary and middle schools were initiated in 1996, and others continue through medical education and residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…A number of studies also confirm the role of ethnicity in medical school admissions and academic attainment (Rosenfeld et al 1992;Esmail et al 1995;McManus et al 1995;Ready 1995;Crump et al 1999;Tekian 1997;Girotti 1999;Hardy 1999;Lumb & Vail 2000;Giordani et al 2001;Ferguson et al 2002). These studies suggest that it is important to consider ethnic status as a possible confounding variable for a fair assessment of the predictive validity of personality measures in medical education.…”
Section: (8) Volunteer Biasmentioning
confidence: 89%
“…A number of studies also confirm the role of ethnicity in medical school admissions and academic attainment (Rosenfeld et al 1992;Esmail et al 1995;McManus et al 1995;Ready 1995;Crump et al 1999;Tekian 1997;Girotti 1999;Hardy 1999;Lumb & Vail 2000;Giordani et al 2001;Ferguson et al 2002). These studies suggest that it is important to consider ethnic status as a possible confounding variable for a fair assessment of the predictive validity of personality measures in medical education.…”
Section: (8) Volunteer Biasmentioning
confidence: 89%
“…In addition, the Robert Wood Johnson Foundation and the W.K. Kellogg Foundation have jointly funded the Health Professions Partnership Initiative program, which was developed from the Project 3000 by 2000 of the Association of American Medical Colleges (Crump et al, 1996;Carline and Patterson, 2003).…”
Section: Developing Leadership Interventions: Learning From the Us Initiativesmentioning
confidence: 99%
“…Our experience with an on-site summer program and knowledge of similar postbaccalaureate programs (Murray-Garcia & Garcia, 2002;Parrish, Daniels, Hester, & Colenda, 2008;McDougle, Way, & Yash, 2008;Blakely & Broussard, 2003;Giordani et al, 2001;Crump, Byrne, & Joshua, 1999;McGlinn, Jackson, & Bardo, 1999;Thomson, Ferry, King, Martinez-Wedig, & Michael, 2003;Lieberman et al, 2010) indicated that students would need didactic materials, a path through the 12 weeks of the program, encouragement to continue, feedback on their progress, and a sense of community.…”
Section: Elements Of the Programmentioning
confidence: 99%
“…For many years, United States federal and state funds have supported premedical enrichment programs to encourage minority and disadvantaged students to pursue medical careers. Traditional programs have embraced bringing the students to medical school campuses and exposing them to the medical school experience which includes, but is not limited to, meeting the faculty, experiencing medical courses, shadowing of a diverse realm of specialties, and admission advice (Murray-Garcia & Garcia, 2002;Parrish, Daniels, Hester, & Colenda, 2008;McDougle, Way, & Yash, 2008;Blakely & Broussard, 2003;Giordani et al, 2001;Crump, Byrne, & Joshua, 1999;McGlinn, Jackson, & Bardo, 1999;Thomson, Ferry, King, Martinez-Wedig, & Michael, 2003;Lieberman, et al, 2010). This may also be accompanied by intense academic preparation for the Medical College Admissions Test (MCAT), a standardized test of academic preparation for medical school in the United States (McGaghie, 2002).…”
Section: Programs To Prepare Underrepresented Students For Success Inmentioning
confidence: 99%